SAFI HALAL COSMETIC PRODUCT PURCHASING DECISION THROUGH BUYING INTEREST AS AN INTERVENING VARIABLE - Yulinda Darwayanti (Universitas Negeri Surabaya, 2025)
The primary goal of this research is to identify the factors that influence purchase decisions on SAFI halal cosmetic items through the use of associative quantitative methods and intervention through buying interest variables. By distributing survey questions, the instruments employed in earlier studies were used to gather the necessary data. Data processing and analysis were carried out using SMART PLS version 3 software. From SAFI's Instagram followers, 100 responders provided the research data. Path analysis reveals that viral marketing, brand religiosity image, lifestyle, and halal certification all have a substantial impact on purchase decisions via buying interest. Meanwhile, beauty vloggers have no discernible influence on shopping decisions via purchasing interest. This means that beauty vloggers have a direct influence on purchasing decisions without passing via buying interest. As a result, SAFI companies should improve their purchase of SAFI products by expanding viral marketing, brand religiosity image, beauty vlogger, lifestyle, halal certification, and buying interest